Novel chlorinated and nitrogenated azaphilones with cytotoxic activities from the marine algal-derived fungus Chaetomium globosum 2020HZ23 - Gao, Zhong-Jie; Cao, Lu-Lu; Ren, Hai-Ping; Yu, Hua; Wang, Yan (Frontiers in Microbiology, 2023)
novel chlorinated and nitrogenated azaphilones, namely N-butyl-2-aza-2-deoxychaetoviridin A (1) and N-hexyl-2-aza-2-deoxychaetoviridin A (2), along with a previously identified analogue, chaetoviridin A (3), were successfully obtained from Chaetomium globosum 2020HZ23, a marine algal-sourced endophytic fungus. The planar structures as well as the absolute configurations of these new metabolites were determined utilizing a synergistic approach that involved both spectroscopic techniques (1D/2D NMR and HRESIMS) and Density Functional Theory (DFT) calculations. Each compound was subject to in vitro cytotoxicity evaluation toward the A549 cancer cell line.Both compounds 1 and 2 demonstrated significant cytotoxicity, as evidenced by their respective IC 50 values of 13.6 and 17.5 μM. Furthermore, 1 and 2 demonstrated potent cell migration inhibition, which elevated with increasing dose concentration. In contrast, compound 3 exhibited less cytotoxic activity relative to 1 and 2, suggesting that the cytotoxic potency escalates with N-substitution at the C-2 position and the introduction of a side chain. This finding could offer implications for future studies aimed at designing and refining lead compounds within this class.